THE EFFECTIVENESS OF THE NEXT GENERATION SOCIAL WELFARE INFORMATION SYSTEM (SIKS-NG) APPLICATION IN MANAGING POVERTY DATA IN SIMOANGIN-ANGIN - Agustin, Nanda Adelia Nur; Agustina, Isna Fitria (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to examine the effectiveness of the implementation of the SIKS-NG application in managing poverty data in Simoangin-angin Village, Wonoayu Sub-district, Sidoarjo Regency, using Richard M. Steers’ effectiveness theory with indicators covering goal attainment, integration, and adaptation. Method: This research employs a qualitative descriptive approach with data collection techniques consisting of interviews, observation, and documentation. Data analysis was carried out using the framework of Miles and Huberman, which includes data collection, data reduction, data presentation, and conclusion drawing. Results: The findings indicate that user adaptation to the application has improved over time; however, training for operators is still lacking. In terms of goal attainment, the results are not yet fully optimal because some beneficiary data remain unverified by the village, particularly those originating from independent proposals. Regarding integration, the community’s proposal process has been in accordance with field procedures, yet socialization efforts to the community are still limited. Novelty: The novelty of this study lies in examining the effectiveness of the SIKS-NG application at the village level, specifically in Simoangin-angin Village, where no in-depth study has previously been conducted.